A comprehensive review of doping in perovskite nanocrystals/quantum dots: evolution of structure, electronics, optics, and light-emitting diodes. (June 2019) - Xu, L.; Yuan, S.; Zeng, H.; Song, J.
Abstract: The explosive development of lead halide perovskite (LHP) nanocrystals (NCs)/quantum dots (QDs) in light-emitting diodes (LEDs) has been witnessed in the past years, because of the direct bandgap, narrow bandwidth, tunable bandgaps, long charge diffusion length, and high carrier mobility. Doping perovskite ABX3 with targeted ions could tune the crystalline structure, electronic structure, luminescence properties, radiative recombination dynamics, and electrical features, which would result in the enhancement of device performances. Recently, there have been amounts of researches about doped perovskite, including A-site, B-site, and X-site dopants, but no report has summarized a comprehensive review of doping in perovskite nanocystals/QDs and the effect of doping on LEDs. In this review, we summarized an overview of recent progress in the effects of A-site, B-site, and X-site doping ions on LHP NCs/QDs. We outline the effects of dopants on crystal structure, optical bandgaps, electronic structure, photoluminescence, carrier dynamics and the application of doped perovskite NCs/QDs in LEDs. The review demonstrates doping in different sites exhibit diverse effects; thus, targeted doping is important to control and improve the material properties and device performances. We conclude that doping is a promising option for improving the device efficiency and stability and give a potential outlook in the field of doped perovskite NCs/QDs. Graphical abstract: Image 1